2015
DOI: 10.1088/0953-4075/48/14/144029
|View full text |Cite
|
Sign up to set email alerts
|

Review of highly charged tungsten spectroscopy research using low energy EBITs at the Shanghai EBIT laboratory

Abstract: We present an overview of recent work on the spectroscopy of tungsten ions, related to tokamak edge plasma. The spectra were recorded from the newly-built low energy electron beam ion traps (EBITs) in the Shanghai EBIT laboratory. By analyzing the spectra with the help of accurate theoretical calculations, using state-of-the-art techniques, we were able to identify term and fine structure splittings in the ground and the first excited configuration for a number of charge states. The theoretical models included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…They confirmed that the ground state is 4f 13 5s 2 2 F 7/2 . Qiu et al [29] studied the visible and soft X-ray spectral regions and concluded that 4f collapse is not complete in W 13+ . According to them [29], four lines that were identified in the Berlin EBIT spectra [30] do not appear to originate from tungsten.…”
Section: Pm-like W (W 13+ )mentioning
confidence: 99%
See 1 more Smart Citation
“…They confirmed that the ground state is 4f 13 5s 2 2 F 7/2 . Qiu et al [29] studied the visible and soft X-ray spectral regions and concluded that 4f collapse is not complete in W 13+ . According to them [29], four lines that were identified in the Berlin EBIT spectra [30] do not appear to originate from tungsten.…”
Section: Pm-like W (W 13+ )mentioning
confidence: 99%
“…Qiu et al [29] studied the visible and soft X-ray spectral regions and concluded that 4f collapse is not complete in W 13+ . According to them [29], four lines that were identified in the Berlin EBIT spectra [30] do not appear to originate from tungsten. Kobayashi et al [31] observed extreme ultraviolet and visible spectra of W 13+ using EBIT.…”
Section: Pm-like W (W 13+ )mentioning
confidence: 99%
“…Detailed laboratory measurements on tungsten ions are well suited for electron beam ion traps (EBITs), where charge-state selection is good and the ion temperature and electron density low. Several studies of tungsten in various ionization stages and spectral ranges have been conducted using EBITs; see, e.g., [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Although designed to have a very wide electron-beam energy range, EBITs have mostly been used at energies above several hundred electron volts, leading to a focus on highly or moderately charged ions with little attention on the first few charge states.…”
Section: Introductionmentioning
confidence: 99%
“…Electron-beam ion traps (EBITs) are one of the most versatile light sources for studying W spectroscopy (see, e.g., Refs. [20,[36][37][38][39][40]), since W ions in almost any charge state can be produced through successive ionization by a monoenergetic and energy-adjustable electron beam. However, the determination of charge states of lowly charged W ions is an intractable problem in EBIT measurements (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years some progress has been made in spectroscopic data for lowly charged W ions (gap for W 7+ -W 26+ ), including W 7+ [4,33,34,36,46,47,48], W 11-15+ [24][25][26][27], and W 25-26+ [37,39]. In the present work we focus on the visible spectra lines from W 8+ , a more complicated case than W 7+ .…”
Section: Introductionmentioning
confidence: 99%